2022
DOI: 10.1590/1677-5449.202102022
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of surgical treatment of varicose veins in Brazil from 2010 to 2020

Abstract: Background Varicose veins have become more common over recent years and in the most serious cases surgical treatment is necessary to resolve patients’ clinical status. Despite their importance, there are no epidemiological studies that cover the whole of Brazil, showing how surgery to correct varicose veins conducted by the Unified Health System (SUS) is distributed in the country. Objectives To describe the ecological profile of surgical treatment to correct varicose veins in Brazil from 2010 to 2020. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Copyright: ©2024 Imbelloni et from 2010 to 2020, 755,752 surgeries were performed to treat varicose veins, of which 292,538 were unilateral (38.71%) and 463,214 (61.29%) were bilateral. 2 A recent systematic review showed that there is evidence of low to moderate quality to suggest that minimally invasive treatments, including foam sclerotherapy, laser, and radiofrequency are comparable to conventional surgery, regarding their effectiveness and safety in treating lower-limb varicose veins. 3 In a recent article, we showed that spinal anesthesia is much more than the use of a single injection of hyperbaric bupivacaine.…”
Section: Meaningmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright: ©2024 Imbelloni et from 2010 to 2020, 755,752 surgeries were performed to treat varicose veins, of which 292,538 were unilateral (38.71%) and 463,214 (61.29%) were bilateral. 2 A recent systematic review showed that there is evidence of low to moderate quality to suggest that minimally invasive treatments, including foam sclerotherapy, laser, and radiofrequency are comparable to conventional surgery, regarding their effectiveness and safety in treating lower-limb varicose veins. 3 In a recent article, we showed that spinal anesthesia is much more than the use of a single injection of hyperbaric bupivacaine.…”
Section: Meaningmentioning
confidence: 99%
“…4 There are several techniques for treating varicose veins. [1][2][3] Being the most serious and operated on in the SUS system, they normally require anesthesia, with spinal anesthesia being the most used. When the patient does not have the saphenous vein removed, the patient can be operated initially in the prone position and later completed in the supine position.…”
Section: Meaningmentioning
confidence: 99%